Experimental and theoretical high pressure study of calcium hydroxyaluminate phases - Cuesta-García, Ana María; Pawel, Rejmak; Ayuela, Andrés; Gómez-de-la-Torre, María de los Ángeles; Santacruz-Cruz, María Isabel; Carrasco, Lucia F.; Popescu, Catalin; García-Aranda, Miguel Ángel (Elsevier, 2017)
Five calcium hydroxyaluminate phases have been investigated by synchrotron powder diffraction at high-pressure: two hydrogarnets, kuzelite, stratlingite and ettringite. The obtained bulk modulus, K0, for kuzelite, stratlingite and ettringite were 23(1), 27(1) and 30(3) GPa, respectively. Kuzelite and stratlingite underwent transformations above 1 GPa likely releasing interlayer water. Kuzelite becoming markedly amorphous and stratlingite remained crystalline, K0= 58(6) GPa in the 1.5–5.5 GPa pressure range. The structural behavior for hydrogarnet samples is prone to the use of pressure transmitting media. K0 for Ca3Al2(OH)12 was 81(2) and 76(2) GPa for silicone oil and alcohol mixture, respectively. A similar study for Ca3Al1.7Fe0.3(OH)12 yielded 73(1) and 58(1) GPa for silicone oil and alcohol mixture, respectively. Atomistic calculations using periodic Density Functional Theory showed that the softening in iron-doped katoite, when compared to stoichiometric katoite, can be assigned primarily to greater compressibility of Ca\\O dodecahedra, which overcompensates strengthening of hydrogen bonding between Al/Fe hydroxide groups.
Keywords: Sincotrones; Cristalografía por rayos X; X-ray synchrotron radiation; Atomistic simulations; Mechanical properties; Hydrogarnet; AFm; AFt